Examining the optimal cutoff values of HADS, PHQ‐9 and GAD‐7 as screening instruments for depression and anxiety in irritable bowel syndrome. Issue 12 (3rd May 2021) - Snijkers, Johanna T. W.; van den Oever, Wendy; Weerts, Zsa Zsa R. M.; Vork, Lisa; Mujagic, Zlatan; Leue, Carsten; Hesselink, Martine A. M.; Kruimel, Joanna W.; Muris, Jean W. M.; Bogie, Roel M. M.; Masclee, Ad A. M.; Jonkers, Daisy M. A. E.; et al.
Abstract: Background: Self‐rating scales are frequently used to screen for anxiety and depression in patients with irritable bowel syndrome (IBS). Different cutoff values are recommended in literature, and guidelines have suggested the use of other screening instruments over time. The aim of this study was to assess the correlation between the most commonly used psychological screening instruments for anxiety and depression in IBS and to compare custom cutoff scores for these instruments. Methods: Irritable bowel syndrome patients ( n  = 192) completed several questionnaires including the Hospital Anxiety and Depression Scale (HADS, HADS‐A and HADS‐D subscale), Patient Health Questionnaire‐9 (PHQ‐9) and Generalized Anxiety Disorder‐7 (GAD‐7). Agreement at different cutoff points, for depressive and anxiety disorder, was assessed by use of the Gwet AC1 coefficient. Key Results: Hospital Anxiety and Depression Scale (HADS)‐D and PHQ‐9 scores, and HADS‐A and GAD‐7 scores showed high correlations (rs  = 0.735 and rs  = 0.805, respectively). For depressive disorder, a Gwet AC1 value of 0.829 was found when recommended cutoff points from literature were compared (PHQ‐9 cutoff ≥10, HADS‐D cutoff ≥8). For anxiety disorder, a Gwet AC1 value of 0.806 was found when recommended cutoff points from literature were compared (GAD‐7 cutoff ≥10, HADS‐A cutoff ≥8). Even higher agreements were found when higher HADS cutoff values were chosen, with impact on sensitivity and specificity. Conclusions & Inferences: Custom cutoff values deem the HADS subscales (HADS‐D and HADS‐A) concordant to PHQ‐9 and GAD‐7 scores. The choice of a cutoff value has substantial impact on sensitivity/specificity and is dependent on patient population, setting, and the purpose of use. Abstract : Comparing cutoff values of self‐rating scales to screen for anxiety and depression in IBS.